SCADA: SUPERVISORY CONTROL AND DATA ACQUISITION (International Journal of Engineering and Computer Science, 2014)
This paper presents a survey on SCADA: Supervisory Control And Data Acquisition. This discussion is centered on overview of SCADA, History of SCADA, security issues, security in SCADA, application of SCADA, operation of SCADA .SCADA systems perform data collection and control at the supervisory level. Some SCADA systems only monitor without performing controlling functions, but these systems are still referred to as SCADA systems